The Correlation Pop Up Book Simadu with Students attention in Natural and Sosial Sciences (IPAS) at Grade IV elementary School - Nurfajrina Mawaddah Rahma; Dita Prihatna Wati (Inovasi Kurikulum, 2025)
The ability of students to focus during learning is a determinant of learning success, but observations at SD Islam Ruhama Ciputat show that the dominance of the monotonous lecture method reduces the quality of learning in Natural and Social Sciences (IPAS). This study aims to examine the use of Pop-Up Book Simadu media in increasing the attention of grade IV students in IPAS learning and the relationship between the use of these media and students' learning attention. Pop-Up Book is considered as potential learning media because it can facilitate the understanding of abstract concepts with a three-dimensional format. This study used a quantitative approach with a correlational method. Data were collected through questionnaires from 26 learners. Data analysis procedures include instrument validity and reliability tests, as well as hypothesis testing using regression analysis and the F test. The results showed that the instruments used had high validity and reliability. The findings indicate a significant relationship between the use of Pop-Up Book Simadu media and increased learner attention in IPAS learning. This media is recommended as an alternative to contextual learning, especially in delivering material about the life cycle of organisms, so that learning becomes more interactive and meaningful.   Abstrak Kemampuan peserta didik untuk fokus selama pembelajaran sebagai penentu keberhasilan belajar, namun observasi di SD Islam Ruhama Ciputat menunjukkan bahwa dominasi metode ceramah yang monoton menurunkan kualitas pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS). Penelitian ini bertujuan mengkaji penggunaan media Pop-Up Book Simadu dalam meningkatkan perhatian peserta didik kelas IV pada pembelajaran IPAS dan hubungan antara penggunaan media tersebut dengan perhatian belajar peserta didik. Pop-Up Book dinilai sebagai media pembelajaran potensial karena mampu memudahkan pemahaman konsep abstrak dengan format tiga dimensi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Data dikumpulkan melalui kuesioner kepada 26 peserta didik. Prosedur analisis data meliputi uji validitas dan reliabilitas instrumen, serta uji hipotesis menggunakan analisis regresi dan Uji F. Hasil penelitian menunjukkan bahwa instrumen yang digunakan memiliki validitas dan reliabilitas tinggi. Temuan ini menunjukkan adanya hubungan signifikan antara penggunaan media Pop-Up Book Simadu dan peningkatan perhatian peserta didik dalam pembelajaran IPAS. Media ini direkomendasikan sebagai alternatif pembelajaran kontekstual, khususnya dalam menyampaikan materi tentang siklus hidup organisme supaya pembelajaran menjadi lebih interaktif dan bermakna. Kata Kunci: buku pop-up; hubungan media; pembelajaran siklus makhluk hidup